Propuesta para disminuir el desempleo en Huajuapan, Oaxaca - Santa Anna Gutiérrez, Pastor Obdulio (2026)
The Heroic City of Huajuapan de León is one of the municipalities of Oaxaca reporting great population growth; according to INEGI’s Intercensal Survey 2015, it has a population of 77,547 inhabitants, with an annual population growth of 2.3%. This has generated the need to create more sources of employment. Therefore, it is necessary to create a proposal from the formal trade to reduce unemployment in the aforementioned municipality.